Optimal Mechanisms for Income Transfer: Note - Schlenker, Robert E. (American Economic Review, 1973)
In a recent article in this Review, Richard Zeckhauser examines the subject of income transfer and concludes that a wage subsidy scheme (WS) is superior to a negative income tax plan (NIT). Zeckhauser's results are derived from a model in which a single representative poor man faces a single, fixed wage rate. The purpose of this comment is to extend Zeckhauser's discussion by comparing the two plans in a setting of many potential recipients, some unemployable and the rest facing different wages rates. When this is done, the superiority of the WS approach over the NIT does not appear quite as clear-cut as suggested in Zeckhauser's article. The many-recipient setting requires two modifications in Zeckhauser's WS plan. First, a positive income floor is needed to cover those who are unemployable or who can work only a small number of hours. Under the scheme presented in Zeckhauser's article, with a negative basic stipend, such individuals would actually be taxed to subsidize the more affluent poor. Second, the subsidy must vary with the wage rate in such a way as to provide a smooth transition from subsidized and unsubsidized rates. The NIT deals with both those problems by providing an income floor and a break-even earnings level at which the subsidy ceases. Zeckhauser is also well aware of the problems and, with Peter Schuck, has suggested a realistic operational WS plan in another writing. The structure of that plan forms the basis for our subsequent discussion.